2017
DOI: 10.1080/14786419.2017.1324959
|View full text |Cite
|
Sign up to set email alerts
|

Xylastriasan A, a new cytochalasan from the fungus Xylaria striata

Abstract: Xylastriasan A (1), a new cytochalasan alkaloid with a rare 5/6/6/5/6 pentacyclic skeleton, and ergosterol (2) were isolated from the ethanol extract of fruiting bodies of the fungus Xylaria striata. Their structures were determined by analysis of their spectroscopic data. Compound 1 exhibited weak cytotoxic activity against HEPG2, B16 and A549 cell lines with IC values of 93.61, 85.61 and 91.58 μM, respectively. Ergosterol (2) potentiated pentobarbital-induced sleep by not only increasing the number of fallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…The correlations between H‐13 with H‐19 and H‐26 ( Figure 2) suggested that H‐13, H‐19, and H‐26 were oriented in the same direction, rings C/D were cis‐ fused and the oxygen bridge was oriented outward. The NOESY signals of H‐8/H‐25, and H‐18/H‐20 also confirmed the above conclusion of the relative configurations on rings C, D and E [13] …”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The correlations between H‐13 with H‐19 and H‐26 ( Figure 2) suggested that H‐13, H‐19, and H‐26 were oriented in the same direction, rings C/D were cis‐ fused and the oxygen bridge was oriented outward. The NOESY signals of H‐8/H‐25, and H‐18/H‐20 also confirmed the above conclusion of the relative configurations on rings C, D and E [13] …”
Section: Resultssupporting
confidence: 79%
“…APT and HSQC spectra revealed the presence of four methylene groups at δ(C) 47.4 (C‐10), 39.6 (C‐15), 29.5 (C‐17), 43.0 (C‐20), eight methine groups at δ(C) 51.9 (C‐3), 51.7 (C‐4), 34.8 (C‐5), 36.6 (C‐8), 44.6 (C‐13), 31.3 (C‐16), 41.4 (C‐19), 24.8 (C‐22) and three quaternary carbons at δ(C) 64.0 (C‐9), 80.9 (C‐14), and 139.5 (C‐6). The above data suggested 1 to be a cytochalasan type alkaloid having a pentacyclic structure [12,13] …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The experiments were performed in triplicate, and the data were averaged. To study the effect of peptides P1 and P2 on bacterial membrane integrity, 4′,6‐diamidino‐2‐phenylindole dihydrochloride (DAPI) and propidium iodide (PI) were used . Briefly, the bacterial cultures at mid‐log phase were incubated with peptide P1 and P2 at 250 μg/mL concentration against E. coli as well as 400 μg/mL for K .…”
Section: Methodsmentioning
confidence: 99%
“…It was used as folk medicine in China [7]. After finding its diverse biological activities in the preliminary screening of large numbers of edible and medicinal mushrooms, our research group started a systematic study on Xylaria striata from cultivation method to chemical components since 2013 [8][9]. These research results clarified its effect of anti-animal and plant pathogens [10], anti-tumor [11], and promoting sleep [12].…”
Section: Introductionmentioning
confidence: 99%